Assessing Holocene Evolution of the Parnaiba River Delta using Petrophysical, Radiocarbon Dating, and Sedimentological Analysis - Cruz, Diogo Bittencourt Leite Tinoco; Vital, Helenice; Aquino da Silva, André Giskard; Stattegger, Karl; Gois Smith, Fernando Sergio; Perez, Yoe Alain (Quaternary and Environmental Geosciences, 2023)
The Parnaíba River Delta, located in northeastern Brazil, is one of the few examples of a deltaic depositional system with its pristine characteristics well preserved. This has placed it the spotlight of scientific research for the most diverse areas. The present work aimed to identify changes in the depositional environment based on stratigraphic and sedimentological analysis. Vibracores were collected in several places such as an old mangrove forest, in active tidal channels and supratidal swamp zones. The study included sediment analysis associated with petrophysics (Gamma Ray Spectrometry) and age dating by the radiocarbon method. In the first phase, the gamma-ray spectral analysis and the photographic record of the cores were carried out, followed by the stratigraphic description (color, texture, presence of organic matter, fossil content, sedimentary structures), as well as the identification and selection of material for dating. Subsequently, the cores were sampled at regular intervals, every 4 cm, for grain size, compositional (organic matter and calcium carbonate quantification), and mineralogical analyses. The results obtained showed mineralogical variations, which indicate changes in sedimentary origin. The gamma-spectrometric data tend to show higher values with the decrease of the grain and are associated with the sedimentological, stratigraphic, and mineralogical data, improving the interpretation of the depositional history. The contents of organic matter and calcium carbonate, in general, presented variations related to the grain size, with fine sediments (fine sand, silt and clay) presenting higher contents of organic matter, while carbonate is related to the presence of shells. Datings showed ages ranging from 4057± 22 BP to recent (1950 AD). The integration and joint analysis of the data allowed a better interpretation of the Late Holocene evolution of the old channels of the Parnaiba river that are currently working as a system of tidal channels.